Die Studientitelanerkennung in der EU - Anwendungen in der Grenzregion Südtirol - Staffler, Christian (bu,press, 2023)
The volume sheds light on the close connection between the recognition of study titles in the EU and the cross-border mobility of EU citizens. The EU, which does not have competences in the field of education, but in the area of the fundamental personal freedoms of the internal market (free movement of workers, freedom of establishment and freedom to provide services), can adopt regulations that ensure the exercise of these fundamental freedoms and thus facilitate cross-border mobility. A special situation arises in the border region of South Tyrol, which has a common language and a common historical development with Austria. For the first time, this volume shows the significant advantage for students from South Tyrol of the so-called change of grades, an international agreement on the mutual recognition of academic degrees between Austria and Italy, beyond EU regulations.